Uji Viabilitas Polen Tanaman Kedelai (Glycine max (L.) Merril) pada berbagai Lama Penyimpanan - Hastya Tri Andini; Muachiroh Abbas; Kamsinah kamsinah (Fakultas Biologi Universitas Jenderal Soedirman, 2022)
Soybean (Glycine max (L.) Merril) is one of the most important grain-producing crops after rice, wheat, millet and barley. Pollen is a male gametophyte produced by seed plants. Pollen can be used for plant identification because it has a distinctive structure and ornamentation, besides that it can also be used as a plant breeding agent as a contributor to male parental characters. The character of pollen as parental male is very important in plant breeding. One way to know the quality of pollen is to look at its viability. Pollen viability can be tested by staining method or by germination method. Pollen viability is known to be lost over a certain period of time. The purpose of this study was to determine the effect of storage time on viability of soybean pollen, and to determine the best storage period with the highest viability of soybean pollen. This research was conducted experimentally with a Completely Randomized Design (CRD) consisting of 4 treatments, namely P0, Control. P1, 7 days of storage. P2, 14 days of storage. P3, 21 days of storage. The independent variable is variation in storage time while the dependent variable is pollen viability. The parameters observed were the number of stained pollen, germination capacity, and the length of the germinating pollen tube as evidence that the pollen was viable. The research data obtained were analyzed using Analysis of Variance (ANOVA) with an error rate of 5%, then continued with the BNT test with an error rate of 5%. The results showed that the provision of storage time treatment on soybean pollen had an effect on pollen viability, namely by reducing pollen viability. The best shelf life to get the highest pollen viability in soybean pollen is 0 to 7 days after the sample is taken.